Quantitative prediction of photoluminescence quantum yields of phosphors from first principles. Issue 2 (19th November 2015) - Escudero, D.
Abstract : The first quantitative prediction of the photoluminescence quantum yields (PLQY) of a series of blue-to-green Ir(iii ) complexes is presented. Abstract : Optimizing the photoluminescence quantum yields of Ir(iii ) complexes is the key to their application as phosphors in organic light-emitting diodes (OLEDs). This work demonstrates for the first time that quantitative predictions of photoluminescence quantum yields (PLQY) in a series of blue-to-green Ir(iii ) complexes can be derived exclusively from electronic structure calculations.